La música tradicional ecuatoriana y su incidencia en el proceso de enseñanza-aprendizaje de conjunto instrumental de estudiantes de guitarra del nivel básico medio del colegio de artes “Salvador Bustamante Celi” de la ciudad de Loja, año lectivo 2018 – 2019. - Gonzalez Benitez, Nelson Leonadro (2019)
This document reflects the alternative guidelines of a proposal to include traditional Ecuadorian music in the teaching-learning process of the Instrumental Ensemble Course of the guitar students of the Middle Basic level of the Salvador Bustamente Celi College of Arts. The proposal contains methodological guidelines for guitar learning based on the constructivist approach. Thus, prior to the approach of the methodological strategies, a preliminary study was carried out with compilation of statistical data, to determine the incidence factors of traditional Ecuadorian music and what is its impact on the learning of the guitar. Then, for the approach of the proposal, the factors derived from the statistical research and the guidelines issued by the Ministry of Education through the Supplementary Baccalaureate Music Curriculum were considered to adapt the academic activities of the students with a repertoire of traditional Ecuadorian music. . Finally, the public socialization of the musical arrangements was carried out, in addition to the results obtained in relation to the objectives set and to define premises with them as conclusions and recommendations.